Association of diabetes with outcomes in patients undergoing contemporary percutaneous coronary intervention: Pre-specified subgroup analysis from the randomized GLOBAL LEADERS study. (February 2020) - Chichareon, Ply; Modolo, Rodrigo; Kogame, Norihiro; Takahashi, Kuniaki; Chang, Chun-Chin; Tomaniak, Mariusz; Botelho, Roberto; Eeckhout, Eric; Hofma, Sjoerd; Trendafilova-Lazarova, Diana; Kőszegi, Zsolt; Iñiguez, Andres; et al.
Abstract: Background and aims: Diabetes has been well recognized as a strong predictor for adverse outcomes after percutaneous coronary intervention (PCI), however, studies in the era of drug-eluting stent and potent P2Y12 inhibitors have shown conflicting results. We aimed to assess ischemic and bleeding outcomes after contemporary PCI according to diabetic status. Methods: We studied 15, 957 patients undergoing PCI for stable or acute coronary syndrome in the GLOBAL LEADERS study with known baseline diabetic status. The primary endpoint was all-cause death or new Q-wave myocardial infarction at 2 years. The secondary safety endpoint was major bleeding defined as bleeding academic research consortium (BARC) type 3 or 5. Results: A quarter of the study cohort were diabetic (4038/15, 957), and these patients had a significantly higher risk of primary endpoint at 2 years compared to non-diabetics (adjusted hazard ratio [HR] 1.38; 95% confidence interval [CI] 1.17–1.63). The difference was driven by a significantly higher risk of all-cause mortality at 2 years in diabetics (adjusted HR 1.47, 95% CI 1.22–1.78). The risk of BARC 3 or 5 bleeding was comparable between the two groups (adjusted HR 1.09, 95% CI 0.86–1.39). The antiplatelet strategy (experimental versus reference strategy) had no significant effect on the rates of primary endpoint and secondary safety endpoint at 2 years in patients with and without diabetes. Conclusions: Diabetic patients had higher risk of ischemic events after PCI than non-diabetic patients, whilst bleeding risk was comparable. The outcomes of diabetic patients following PCI were not affected by the two different antiplatelet strategies. Graphical abstract: Image 1 Highlights: Diabeticstreated with contemporary PCI still had a higher risk of adverse ischemic events compared to non-diabetics The risk of bleeding and stent thrombosis was comparable amongst non-diabetics and diabetics. Long-term ticagrelor monotherapy did not affect the outcomes of diabeticsfollowing percutaneous coronary intervention.